ADVANTAGES OF USING VMI LOGISTICS TECHNOLOGY IN THE SUPPLY CHAIN: https://doi.org/10.5281/zenodo.15406829 - Rakhmonov , Asadbek (Journal of Contemporary World Studies, 2025)
This article analyzes the advantages of using VMI (Vertical Market Integration) logistics technologies in the supply chain. VMI technology, the automatic management and supply of goods in the supply chain, helps to strengthen the relationship between each department. In this system, the manufacturer or supplier monitors the needs of the customer in real time and delivers the necessary products to him on time.